PENGARUH KOMITMEN ORGANISASIONAL DAN EMOTIONAL INTELLIGENCE TERHADAP KINERJA GURU DENGAN MEDIASI KEPUASAN KERJA (Studi Pada SMPN Se-Kecamatan Sragi Pekalongan) (Jurnal Mahasiswa Pasca Sarjana, 2014)
This study aimed to examine the effect of organizational commitment and emotional intelligence on performance by mediating teacher job satisfaction ( Study On SMP District of Pekalongan Sragi ) . The population in this study is 114 respondents , sampling in this study using census method . Testing in this research that uses Test Instruments ( Test Validity and Reliability Test ) , Normality Test , Test Assumptions Classical ( Multicollinearity Test and Test Heteroskidastity ) , Test Test model used is Adjusted R2 (coefficient of determination ) and F-test , Hypothesis Testing in research the regression analysis used to test the hypothesis significance level ( α ) of 5% and , test mediation effects with path analysis path . Based on the findings of the study are : Organizational Commitment has a positive and significant impact on job satisfaction , Emotional Intelligence has a positive and significant impact on Job Satisfaction , Organizational Commitment has a positive and significant impact on teacher performance , Emotional Intelligence has a positive and significant impact on teacher performance , job satisfaction has a positive and significant impact on teacher performance , job Satisfaction Organizational Commitment mediates the effect of teacher performance , job satisfaction mediates Emotional Intelligence on teacher performance . Keywords : Organizational Commitment , Emotional Intelligence , Performance Teacher Job Satisfaction